2012
DOI: 10.1242/dev.074856
|View full text |Cite
|
Sign up to set email alerts
|

Theosr1andosr2genes act in the pronephric anlage downstream of retinoic acid signaling and upstream ofwnt2bto maintain pectoral fin development

Abstract: SUMMARYVertebrate odd-skipped related genes (Osr) have an essential function during the formation of the intermediate mesoderm (IM) and the kidney structures derived from it. Here, we show that these genes are also crucial for limb bud formation in the adjacent lateral plate mesoderm (LPM). Reduction of zebrafish Osr function impairs fin development by the failure of tbx5a maintenance in the developing pectoral fin bud. Osr morphant embryos show reduced wnt2b expression, and increasing Wnt signaling in Osr m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 59 publications
(133 reference statements)
6
44
0
Order By: Relevance
“…Consistent with this possibility, murine Osr1 and Osr2 are partially redundant in joint formation where they regulate Wnt4 and Wnt9b expression (Gao et al, 2011), and Osr2 is required to negatively regulate Bmp4 and Msx1 during tooth development ). Furthermore, we have recently found that, in zebrafish, Osr1/Osr2 also regulates wnt2b expression in lpm during fin development (Neto et al, 2012), suggesting that this regulatory cassette is employed in many tissues.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this possibility, murine Osr1 and Osr2 are partially redundant in joint formation where they regulate Wnt4 and Wnt9b expression (Gao et al, 2011), and Osr2 is required to negatively regulate Bmp4 and Msx1 during tooth development ). Furthermore, we have recently found that, in zebrafish, Osr1/Osr2 also regulates wnt2b expression in lpm during fin development (Neto et al, 2012), suggesting that this regulatory cassette is employed in many tissues.…”
Section: Discussionmentioning
confidence: 98%
“…In response to RA signaling, wnt2ba expression is initiated in the intermediate mesoderm (Ng et al, 2002). In turn, Wnt2ba is required for expression of the T-box transcription factor tbx5 in the lateral plate mesoderm (LPM) (Neto et al, 2012). Between the 6-and 15-somite stages (ss; 12-16 hours post-fertilization, hpf) (Kimmel et al, 1995), tbx5-positive cells comprise two bilateral stripes that contain both heart and fin precursors (Ahn et al, 2002; Begemann RESEARCH ARTICLE Ring1b controls fin development and Ingham, 2000; Furthauer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish osr1 is expressed robustly in the ventral head mesenchyme and branchial arches but its role in craniofacial development has not been examined. Osr1 has been shown to be essential for kidney formation [29], and recently has been shown to interact with tbx5a during pectoral fin development [30]. Here we show that osr1 is severely disrupted by loss of tbx22-2 expression.…”
Section: Gene Expression Analysismentioning
confidence: 49%
“…It is more likely that the gdf5 levels are being influenced by another factor independent of bapx1. Osr1 has been shown to be required for maintenance of expression of signaling molecules critical for joint formation, including Gdf5 [30]. This work has also revealed a significant loss of osr1 signaling in tbx22 morphants which positions osr1 as a candidate for mediating the effect of loss of early tbx22 signals in craniofacial development.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation